1990
DOI: 10.1007/bf02274780
|View full text |Cite
|
Sign up to set email alerts
|

Significance of rheumatoid factor isotypes in seronegative rheumatoid arthritis

Abstract: In a cross-sectional study of 124 patients with definite or classical rheumatoid arthritis (RA) and negative agglutination assays, rheumatoid factor (RF) isotypes were measured using an ELISA technique. Elevated levels of IgA-RF were found in 55 patients (44%), IgG-RF in 99 (80%), and IgM-RF in 20 (16%). The levels of IgA- and IgM-RF correlated with each other (P less than 0.001). Elevated levels of IgM-RF were associated with a more severe disease course. Elevated levels of IgA-RF correlated with the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Studies relating RF isotypes RA severity and out-IgG as antigen there was an association between come have given conflicting results; Table VII sum-IgARF and rheumatoid nodules (p<0.02). There marises 25 studies involving 1894 patients (7-10, was no association when horse IgG was antigen 13-16, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Thirteen used rabbit IgG as the ( Table VI ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies relating RF isotypes RA severity and out-IgG as antigen there was an association between come have given conflicting results; Table VII sum-IgARF and rheumatoid nodules (p<0.02). There marises 25 studies involving 1894 patients (7-10, was no association when horse IgG was antigen 13-16, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Thirteen used rabbit IgG as the ( Table VI ).…”
Section: Resultsmentioning
confidence: 99%
“…IgG isotype RF (IgG‐RF) is present in abundant quantities in the joint cavity and undergoes self association into dimers or higher polymers. Some investigators reported that the levels of serum IgG‐RF were related to the disease activity in rheumatoid arthritis (RA); 6–8 others reported to the contrary 9–11 . The clinical significance of IgA‐RF, which can be measured by a similar method to IgG‐RF, has not been well established.…”
mentioning
confidence: 99%
“…Among the features which have been repeatedly associated with more rapid or extensive joint erosion are greater disease activity in the early stages,6 7 the appearance of nodules8 10 and serum levels of IgM-_8 and IgA-rheumatoid factor (RF). [14][15][16][17][18] Previous studies seeking predictors of the radiological course in RA have not included immunohistochemical analysis of the synovial membrane. It is entirely appropriate to study synovial immunohistochemistry as the synovial membrane contains all the interrelated cellular and biochemical elements which lead to tissue destruction.…”
mentioning
confidence: 99%